2007
DOI: 10.1007/s00213-007-1038-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ethanol locomotor sensitization in adolescent and adult DBA/2J mice

Abstract: These results indicate that adolescent mice are less sensitive to ethanol sensitization, and this blunted behavioral response in adolescents might reflect differential ethanol-induced neurobehavioral adaptations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 52 publications
10
59
3
1
Order By: Relevance
“…Regarding the adverse and unpleasant effects of alcohol, a lower sensitivity to the sedative (Little et al 1996;Quoilin et al 2010;Silveri and Spear 1998), ataxic (White et al 2002), and hypothermic (Silveri and Spear 2000) effects of ethanol have been reported in adolescent relative to adult rats and mice. In contrast, adolescent rodents have been shown to be more sensitive than adults to the locomotor stimulant effects of ethanol (Quoilin et al 2010;Stevenson et al 2008) and to ethanol-induced social facilitation (Varlinskaya and Spear 2002).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding the adverse and unpleasant effects of alcohol, a lower sensitivity to the sedative (Little et al 1996;Quoilin et al 2010;Silveri and Spear 1998), ataxic (White et al 2002), and hypothermic (Silveri and Spear 2000) effects of ethanol have been reported in adolescent relative to adult rats and mice. In contrast, adolescent rodents have been shown to be more sensitive than adults to the locomotor stimulant effects of ethanol (Quoilin et al 2010;Stevenson et al 2008) and to ethanol-induced social facilitation (Varlinskaya and Spear 2002).…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies showed that adolescent Swiss mice, in contrast to adults, did not develop locomotor sensitization to ethanol or even show a behavioral tolerance to the locomotor stimulant effects of ethanol after repeated ethanol administrations (CarraraNascimento et al 2011;Faria et al 2008). In another study on DBA/2J mice, Stevenson et al (2008) reported that adolescent mice were less sensitive than adult mice to ethanol-induced sensitization. However, these studies were limited to the comparison of two age groups (adults and adolescents) and low to moderate doses of ethanol (between 1.0 and 2.5 g/kg).…”
Section: Introductionmentioning
confidence: 92%
“…Studies report hyposensitivity (Faria et al, 2008;Stevenson, Besheer, & Hodge, 2008) or hypersensitivity (Hefner & Holmes, 2007) to ethanol's stimulating or sensitizing effects during adolescence, compared to adulthood. We showed that CUS-ETOH adolescents also displayed lower cross-sensitization, compared to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Age can also influence the mechanism of sensitization. This reflects different mechanisms of neurobehavioral adaptations in different groups of ages Stevenson, Besheer, & Hodge, 2008). The activation of accumbal D2 receptors is essential for the expression of signs of behavioral sensitization (Abrahao, Quadros, Andrade, & SouzaFormigoni, 2012).…”
Section: Discussionmentioning
confidence: 99%